Base of Unisphere under construction
Caption, "Tripod-like base on Unisphere, which has been likened to a golf tee, is in position as preliminary work starts on Unisphere. Base supporting Unisphere is made of U.S. Steel's Cor-Ten steel. Supporting the stainless steel globe on the three-legged base has been compared to positioning a beach ball on a golf tee."